Optimal trading strategy during bull and bear markets for Hong Kong-listed stocks - Hui, Eddie C. M.; Chan, Ka Kwan Kevin (International Journal of Strategic Property Management, 2018)
The “buy-and-hold” strategy based on the EMH was believed by many people to be optimal for a long time. However, there has been more criticism on the EMH since the global financial crisis in 2008. Hence many people attempt to find a trading strategy to beat “buy-and-hold”. Moreover, the financial market fluctuates a lot. Sometimes it is in a bull market, but it may be in a bear market during other periods of time, so the optimal strategy during different periods of time may vary and hence switching of strategies may be necessary. In this study, we apply Hui and Chan (2018)’s generalized time-dependent strategy on 12 Hong Kong listed stocks during the whole period of observation and two sub-periods. The results show that when the sub-period December 31, 2004–December 31, 2008 is chosen, the strategy outperforms “buy-and-hold” by the largest extent. This reflects that the strategy is most effective during adverse market conditions. This study can help investors to apply appropriate trading strategies to earn more profits, and help property practitioners to improve their strategic property management to increase the value of their portfolio.